Design Of A Semi-Automatic Positioning System For Measuring Of Semiconductor Chips - Kotian, Tomáš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The aim of this work is to design a semi-automatic positioning system for the testof semiconductor chips. The work solves the problems with the implementation of the constructionto achieve the highest possible accuracy for contacting with probe card. Next, the work deals withthe selection of a suitable control unit for stepper motors and finally to create a program to controlthe system and display image from the camera to the computer. The last requirement for the programis detection of chips with the camera image and automatic centering with a probe card.
Keywords: Semi-automatic positioning system for chip test; TMCM-6110; LabWIEW; probecards